ETUDE DESCRIPTIVE ET COMPARATIVE DES GRAPHIQUES DE REUSSITES A L’EXAMEN D’ETAT DE DEUX OPTIONS : MATH-PHYSIQUE ET BIO-CHIMIE DE L’INSTITUT SCIENTIFIQUE DE KISANGANI ;RD Congo. DE 2007 à 2012 - DEPSE, BAENDAENDA SHINDANI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Modern society requires more and more educated men capable of intelligent and original acts. This is why each parent seeks to educate his child in order to provide him with happiness, a well-being in the society in which he is called to play a well-defined role.Each African country has established an education system to improve learning conditions and enable teachers and students to meet their expectations The length of time some people spend in school is often greater than that for a given cycle.Thus, one of the major problems in the education system is that of school drop-out, namely repetition and drop-out. This loss of school results in: the waste of financial resources, banditry in society ... Pedagogically, performance is evaluated in terms of quantity and quality: on the one hand, the number of students trained in relation to the number of students in school counts drop-outs and repetitions on the other hand, the knowledge and skills acquired.Indeed, school assessment seems to be the result of both formal and informal procedures to find out which teachers and students are seeking feedback on their own actions.Many of these procedures occur independently of fixed opportunities and occur in a context of training, impressions and altitudes. In general, four objectives seem to be assigned to school progress: Improve the decisions relating to the learning of each student, Improve the quality of teaching, inform on its progress, the pupil and his parents. The success of students in state examinations is a real stimulus for public power. It is also good for school boards, teachers, parents and students.